PENGARUH METODE YANBU’A TERHADAP KETERAMPILAN MEMBACA AL QUR’AN SISWA DI MI DARUL AMIEN JAJAG - Benny Angga Permadi; Imam Mashuri; Nila Nurul Wasi’ah (AT TA'LIM : Jurnal Madrasah Ibtidaiyah, 2024)
The Yanbu'a method is a method of learning to read and write the Qur'an consisting of 7 Juz which are arranged systematically. In learning, students are required to be active, the way to read it must not be spelling, it must be firm and correct according to the makhraj and tajwid. Meanwhile, students' ability to read the Koran is the hope of Muslim parents. For this reason, it is necessary to have an appropriate method for learning Al Qur'an reading skills for students. Starting from this idea, the problem is whether there is an influence of the Yanbu'a method on students' Al Qur'an reading skills. This research aims to determine the effect of the Yanbu'a method (Variable X) on students' Al Qur'an reading skills (Variable Y) at MI Darul Amien Jajag. Pre-experimental quantitative research with one-group pretest-posttest design type. The population was 22 first grade students and the sampling technique was saturated sampling technique. Research instruments use tests, observations and interviews. The test instrument was tested using validity and reliability tests. Next, a prerequisite test is carried out consisting of a normality test and a homogeneity test used to test the sample. To test the hypothesis, use the T Paired Sample Test with the help of the SPSS 24.00 for Windows computer program. The research results show that the influence of the Yanbu'a(X) method on Al Qur'an (Y) reading skills is empirically 16.609 (Tcount). The data was consulted with df=21 and the significance level was 0.000, the critical price was 2.08596 (Ttable), so the calculation result of Tcount was greater than the critical value Ttable. This means that there is an influence of the Yanbu'a method on students' Al Qur'an reading skills at MI Darul Amien Jajag. Ha is accepted and Ho is rejected.